(untitled) (Nigerian Journal of Technology, 2016)
Completing construction projects entails inputs from various professional disciplines; this makes projects prone to conflicts. It has been acknowledged that management of conflict is crucial to improving project performance. Thus, understanding the causes of conflicts in construction project will ease the process of conflict management. This study sets out to gain an in depth understanding of the causes of conflicts in Nigeria using mixed method research approach. Both questionnaire survey and interview were used to capture the perspective of consultants and contractors on causes of conflicts. Based on the responses, it was evident that poor financial projection on the client’s side is the most significant cause of conflicts. Furthermore, it was found that there are no differences in the perception of both groups of respondents. This finding was also evident from interviews. Thus, there is a need for clients to develop procedures of engaging competent and experienced consultants so as to reduce the likelihood of conflicts. http://dx.doi.org/10.4314/njt.v35i2.8